La mediación de la Organización de la Unidad Africana durante los conflictos del Cuerno de África (1963-1991) - Arconada-Ledesma, Pablo (El Colegio de México, 2021)
This research delves into the role of the Organisation of African Unity (OUA) in the resolution and mediation of conflicts in the Horn of Africa during the Cold War period. Its regional activities over the years in question warrant this analysis given the current controversy surrounding them. By studying this regional institution’s records on the Ogaden conflict (1964), the Shifta War (1963-1967), and the second Ogaden War (1977-1978), the article sheds new light on a specific subject. The research is based on a review of OUA and UN documentary sources, as well as press articles.